2012
DOI: 10.1093/nar/gks594
|View full text |Cite
|
Sign up to set email alerts
|

Toward the identification and regulation of the Arabidopsis thaliana ABI3 regulon

Abstract: The plant-specific, B3 domain-containing transcription factor ABSCISIC ACID INSENSITIVE3 (ABI3) is an essential component of the regulatory network controlling the development and maturation of the Arabidopsis thaliana seed. Genome-wide chromatin immunoprecipitation (ChIP-chip), transcriptome analysis, quantitative reverse transcriptase–polymerase chain reaction and a transient promoter activation assay have been combined to identify a set of 98 ABI3 target genes. Most of these presumptive ABI3 targets require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
183
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(193 citation statements)
references
References 99 publications
8
183
2
Order By: Relevance
“…In Arabidopsis, weak alleles of ABI3 are fully desiccation tolerant but have reduced storability, making it one of the major regulators of longevity (Ooms et al, 1993;Sugliani et al, 2009;Verdier et al, 2013). In wkry3 and nfxl1 mutant seeds, dry weight accumulation and other developmental processes regulated by ABI3, such as chlorophyll degradation and the accumulation of nonreducing soluble sugar contents, were not affected in mature seeds, and NFXL1, WRKY3, or WRKY33 have not been identified as targets of ABI3, LEC1, or LEC2 (Braybrook et al, 2006;Junker et al, 2012;Mönke et al, 2012). In M. truncatula, our transcriptome data on abi3 mutant seeds and ectopic expression of ABI3 using a hairy root system demonstrate that NFXL and WRKY33 transcript levels were not deregulated by ABI3, making these TF putative regulators of an ABI3-independent pathway involved in longevity.…”
Section: Discussion Translational Biology Between M Truncatula and Amentioning
confidence: 99%
“…In Arabidopsis, weak alleles of ABI3 are fully desiccation tolerant but have reduced storability, making it one of the major regulators of longevity (Ooms et al, 1993;Sugliani et al, 2009;Verdier et al, 2013). In wkry3 and nfxl1 mutant seeds, dry weight accumulation and other developmental processes regulated by ABI3, such as chlorophyll degradation and the accumulation of nonreducing soluble sugar contents, were not affected in mature seeds, and NFXL1, WRKY3, or WRKY33 have not been identified as targets of ABI3, LEC1, or LEC2 (Braybrook et al, 2006;Junker et al, 2012;Mönke et al, 2012). In M. truncatula, our transcriptome data on abi3 mutant seeds and ectopic expression of ABI3 using a hairy root system demonstrate that NFXL and WRKY33 transcript levels were not deregulated by ABI3, making these TF putative regulators of an ABI3-independent pathway involved in longevity.…”
Section: Discussion Translational Biology Between M Truncatula and Amentioning
confidence: 99%
“…These proteins include putative ABI3 targets (Mönke et al, 2012) and those related to ABA biosynthesis and signaling (Tables I and II). We also noted changes in the levels for proteins involved in lipid metabolism.…”
Section: An Isobaric Tags For Relative and Absolute Quantitation Expementioning
confidence: 99%
“…We found that several seed storage proteins, including SEED STORAGE ALBUMIN1 (SESA1), SESA12, and SESA3 and two oleosin proteins, were down regulated in the cer9-2 mutant (Table II). These proteins are involved in oil body formation and are also ABI3 putative targets (Mönke et al, 2012; Table II).…”
Section: An Isobaric Tags For Relative and Absolute Quantitation Expementioning
confidence: 99%
“…Recent work using chromatin immunoprecipitation (ChIP) and expression analysis is revealing how some of these factors control development and how they interact (Braybrook et al, 2006;Kaufmann et al, 2009;Zheng et al, 2009;Mönke et al, 2012). Here, we report the genome-wide identification of in vivo binding sites for FUS3 in an embryonic culture tissue system that allows robust ChIP.…”
mentioning
confidence: 98%